Integrating ChatGPT in Higher Education: Insights into Student Usage, Critical Thinking, and Independent Learning - Saputra, Nizar; Asirah, Asirah; Syafitri, Siska Eka (IJELR: International Journal of Education, Language, and Religion, 2025)
This study aims to investigate how university students use ChatGPT in academic contexts and how they perceive its influence on critical thinking and independent learning. Using a descriptive survey method, data were collected from 156 university students through a structured questionnaire covering ChatGPT usage frequency, academic purposes, and perceptions related to critical and independent thinking. The findings reveal that 98.1% of students utilize ChatGPT for academic tasks such as research, essay writing, and problem-solving, with most using it either occasionally (55.1%) or weekly (20.5%). Students reported that ChatGPT supports their ability to analyze information and generate ideas, with over half agreeing that it enhances critical thinking. However, a notable portion also expressed concerns about potential overreliance on AI, suggesting it may hinder independent thought and problem-solving skills. Based on these insights, the study recommends integrating AI literacy into higher education curricula to promote mindful, ethical, and strategic use of tools like ChatGPT. This approach can help students balance the benefits of AI with the development of their autonomous academic skills.